Description of CRISPR-Cas9 development and its prospects in human papillomavirus-driven cancer treatment - Wei, Yuhao; Zhao, Zhen; Ma, Xuelei (Frontiers in Immunology, 2022)
Human papillomaviruses (HPVs) have been recognized as the etiologic agents of various cancers and are called HPV-driven cancers. Concerning HPV-mediated carcinogenic action, gene therapy can cure cancer at the molecular level by means of the correction of specific genes or sites. CRISPR-Cas9, as a novel genetic editing technique, can correct errors in the genome and change the gene expression and function in cells efficiently, quickly, and with relative ease. Herein, we overviewed studies of CRISPR-mediated gene remedies for HPV-driven cancers and summarized the potential applications of CRISPR-Cas9 in gene therapy for cancer.